2017
DOI: 10.5740/jaoacint.16-0184
|View full text |Cite
|
Sign up to set email alerts
|

The Celiac Patient Antibody Response to Conventional and Gluten-Removed Beer

Abstract: Enzymatic digestion, or hydrolysis, has been proposed for treating gluten-containing foods and beverages to make them safe for persons with celiac disease (CD). There are no validated testing methods that allow the quantitation of all the hydrolyzed or fermented gluten peptides in foods and beverages that might be harmful to CD patients, making it difficult to assess the safety of hydrolyzed products. This study examines an ELISA-based method to determine whether serum antibody binding of residual peptides in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…In particular, the Weissbier was the most active on the three CD TCL, which is consistent with the relatively high abundance of specific immunoreactive epitopes. Because of the presence of immunotoxic peptides, the gluten-free beer induced a substantial IFN-γ response, especially in CD#1, in agreement with a previous observation with gluten-reduced beer ( 49 ). Nevertheless, in the case of gluten-free beer the levels of INF-γ was drastically reduced by the simulated GD digestion in one (CD#1), while it increased in CD#2 and CD#3, although these increments were not statistically significant.…”
Section: Resultssupporting
confidence: 91%
“…In particular, the Weissbier was the most active on the three CD TCL, which is consistent with the relatively high abundance of specific immunoreactive epitopes. Because of the presence of immunotoxic peptides, the gluten-free beer induced a substantial IFN-γ response, especially in CD#1, in agreement with a previous observation with gluten-reduced beer ( 49 ). Nevertheless, in the case of gluten-free beer the levels of INF-γ was drastically reduced by the simulated GD digestion in one (CD#1), while it increased in CD#2 and CD#3, although these increments were not statistically significant.…”
Section: Resultssupporting
confidence: 91%
“…On the contrary, many of the recent investigations which employed enzyme‐linked immunosorbent assay (ELISA), mass spectrometry, and Western blot analysis reported that PEP did not thoroughly destroy the whole gluten proteins (Allred et al., 2017; Colgrave et al., 2017; Fiedler et al., 2018; Panda et al., 2015), which indicates that beers treated with PEP are not safe for CD patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, weather the products would pose any risk to individuals that have a high degree of sensitivity towards cereal prolamins still remains to be clarified. Testing for protein binding reactions using sera of active coeliac disease patients may provide additional confirmation for suitability of the food for gluten sensitive consumers (Allred et al, 2017).…”
Section: Gluten Contentmentioning
confidence: 99%